العدول عند المفسر الكوردي أحمد بن إسماعيل الكورانـي (893هـ) الأجزاء الأربعة الأخيرة أنموذجا - عزيز, م. د.فريدون أحمد (Sulaimani Journal for Humanities, 2023)
There is no doubt that the Arabic language is a broad and spacious language, which contains within it multiple linguistic phenomena. One of these phenomena is the (AL-Odwl). In its simplest definition, it is a tendency from the fixed linguistic origin to another expression In order to cherish an aesthetic that would not have been found in the normative constant. We chose to study this phenomenon with a Kurdish scientist, he assumed the position of Sheikh Al-Islam in the Ottoman Sultanate, He is Ahmed bin Ismail Al-Gorani, one of the scholars of the ninth century AH. He dealt with this phenomenon during his interpretation of the Quranic verses. We devoted this research to him and his opinions in order to extract what he sees in the aesthetics of al-odwl. There were more than twenty verses in which this scholar mentioned his opinion on (Al- Odwl), and this research was).
Keywords: الكلمات المفتاحية العدول الكوراني